Brucella MucR acts as an H-NS-like protein to silence virulence genes and structure the nucleoid - Ian S. Barton; Zhongqing Ren; Connor B. Cribb; Joshua E. Pitzer; Ilaria Baglivo; Daniel W. Martin; Xindan Wang; R. Martin Roop (mBio, 2023)
ABSTRACTHistone-like nucleoid structuring (H-NS) and H-NS-like proteins serve as global gene silencers and work with antagonistic transcriptional activators (counter-silencers) to properly coordinate the expression of virulence genes in pathogenic bacteria. In Brucella, MucR has been proposed as a novel H-NS-like gene silencer, but direct experimental evidence is lacking. Here, we show that MucR serves as an H-NS-like silencer of the Brucella abortus genes encoding the polar autotransporter adhesins BtaE and BmaC, the c-di-GMP-specific phosphodiesterase BpdB, and the quorum-sensing regulator BabR. We also demonstrate that the MarR-type transcriptional activator MdrA can displace MucR from the btaE promoter, supporting the existence of MucR counter-silencers in Brucella. Moreover, our chromatin immunoprecipitation (ChIP)-seq analysis identified 546 MucR enrichment peaks along the genome, including in the promoters of the genes encoding the Type IV secretion machinery and effectors and the quorum-sensing regulator VjbR. Importantly, MucR ChIP-seq peaks overlap with the previously described binding sites for the transcriptional activators VjbR, BvrR, and CtrA suggesting that these regulators serve as MucR counter-silencers and work in concert with MucR to coordinate virulence gene expression in Brucella. In addition, using chromosome conformation capture (Hi-C), we show that like H-NS in Escherichia coli, MucR alters the global structure of the Brucella nucleoid. Finally, a copy of the E. coli hns rescues the distinctive growth defect and elevated btaE expression of a B. abortus mucR mutant. Together, these findings solidify the role of MucR as a novel type of H-NS-like protein and suggest that MucR’s gene-silencing properties play a key role in virulence in Brucella.IMPORTANCEHistone-like nucleoid structuring (H-NS) and H-NS-like proteins coordinate host-associated behaviors in many pathogenic bacteria, often through forming silencer/counter-silencer pairs with signal-responsive transcriptional activators to tightly control gene expression. Brucella and related bacteria do not encode H-NS or homologs of known H-NS-like proteins, and it is unclear if they have other proteins that perform analogous functions during pathogenesis. In this work, we provide compelling evidence for the role of MucR as a novel H-NS-like protein in Brucella. We show that MucR possesses many of the known functions attributed to H-NS and H-NS-like proteins, including the formation of silencer/counter-silencer pairs to control virulence gene expression and global structuring of the nucleoid. These results uncover a new role for MucR as a nucleoid structuring protein and support the importance of temporal control of gene expression in Brucella and related bacteria.